PENGARUH AKTIVITAS INDUSTRI TERHADAP KUALITAS AIR SUNGAI KABUPATEN KARAWANG - Akda Zahrotul Wathoni; Nur Qalbi Faagna; Annisa Indah Pratiwi (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
The Citarum River is one of the supports for daily life such as raw materials for clean water by PDAM, irrigation, toilets, water reservoirs, transportation, recreation, irrigation sources for agriculture, industry. These activities, especially industries that have recently developed very quickly, have unwittingly produced liquid and solid wastes that enter the Citarum watershed, so it is suspected that this river has been polluted. The research was carried out at 6 sampling points, namely: Point 1: Anggadita Village; Point 2: Pindodeli Area; Point 3: Telukjambe Bridge; Point 4: Unsika Area; Point 5: Karawang Square: and Point 6: Tanjungpura Purwadana Area. The time of observation is: August 2021-January 2022. This study aims to determine how much influence industrial activity has on river water quality based on the pollution index (Permen LH No.115 of 2003) with correlation and simple regression methods. The results of this study indicate that there is an influence of industrial activity on the decline in water quality of the Citarum River, Kab. Karawang by 95.6%.